2007
DOI: 10.4315/0362-028x-70.12.2889
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E Virus RNA in Commercial Porcine Livers in The Netherlands

Abstract: Human hepatitis E virus (HEV) infections by genotype 3 strains in industrialized countries are hypothesized to be caused by pigs. To examine this hypothesis, the potential health risks of transmission routes should be examined. Possible foodborne transmission was studied by quantifying the presence and infectivity of HEV in commercial porcine livers in The Netherlands. A comparison of four tissue disruption and seven RNA extraction methods revealed that mechanical disruption followed by silica-based RNA extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
138
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(146 citation statements)
references
References 38 publications
7
138
1
Order By: Relevance
“…These reports found much lower HEV RNA-positive samples compared to grocery stores tested in this study, for which the average was 25%. This positivity average was 13-, 4.2-, 2.3-, and 6.3-fold greater than that found in Japan (Yazaki et al, 2003), Holland (Bouwknegt et al, 2007), USA (Faegins et al, 2007), and Germany (Wenzel et al, 2011), respectively. Faegins et al (2007 reported that livers from grocery stores in the US contained HEV RNA.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…These reports found much lower HEV RNA-positive samples compared to grocery stores tested in this study, for which the average was 25%. This positivity average was 13-, 4.2-, 2.3-, and 6.3-fold greater than that found in Japan (Yazaki et al, 2003), Holland (Bouwknegt et al, 2007), USA (Faegins et al, 2007), and Germany (Wenzel et al, 2011), respectively. Faegins et al (2007 reported that livers from grocery stores in the US contained HEV RNA.…”
Section: Discussionmentioning
confidence: 56%
“…Regarding livers from grocery stores for human consumption, HEV RNA was detected in 1.9% (363 samples) of tested livers originating from supermarkets in Japan (Yazaki et al, 2003), 6% (62 samples) of packets of liver in Holland (Bouwknegt et al, 2007), and 11% (127 samples) of packets of liver in the USA (Faegins et al, 2007). Additionally, Wenzel et al (2011) that in 200 liver samples in Germany, 4% were positive for HEV RNA.…”
Section: Discussionmentioning
confidence: 99%
“…In The Netherlands, 4/62 (6 . 5 %) pig livers on retail sale were found positive for HEV RNA and sequencing analysis found HEV gt3 to be closely related to HEV gt3 of pigs (97 %) and humans (93 %) in The Netherlands [44].…”
Section: Potential For Foodborne Zoonotic Transmissionmentioning
confidence: 99%
“…Yazaki et al (2003) investigated a series of 29 cases of sporadic hepatitis E occurring in Japan and identified nine patients with a history of having recently ingested grilled or undercooked pig liver 2-8 weeks before the onset of the disease. Additionally, HEV RNA has been detected in 6.5 and 11% of commercial pig liver in Netherlands and United States, respectively (Bouwknegt et al 2007;Feagins et al 2007). All strains detected were classified as HEV genotype 3.…”
Section: Hev Infection As a Zoonosismentioning
confidence: 99%